Integrated Green Chemical Approach to the Medicinal Plant Carpobrotus edulis Processing - Lyubchyk, Sergiy (2019)
Associate Laboratory for Green Chemistry (LAQV), which is financed by national funds from FCT/MCTES (UID/QUI/50006/2019).